A longitudinal study into the effectiveness of the HPO Framework: The case of a social care and rehabilitation organization. Issue 3 (7th August 2017) - de Waal, André
Abstract : Purpose: The academic and management literature offers an abundance of techniques for helping organizations improve their performance. Generally, though, these techniques have not been subjected to rigorous, evidence-based evaluation or have been tested in practice over time. The purpose of this paper is to describe a longitudinal study into the effectiveness of the High Performance Organization (HPO) Framework at a social care and rehabilitation organization. Design/methodology/approach: The HPO Framework was applied at LIMOR in the Netherlands. The longitudinal nature of the study consisted of conducting an "HPO diagnosis" twice at the organization, in 2012 and 2015. In the second diagnosis, the effectiveness of the interventions the organization undertook to address the recommendations originating from the first HPO diagnosis was also measured. Findings: The study aimed to discover whether the HPO Framework was a suitable improvement technique with which to increase the performance of a social care and rehabilitation organization in a sustainable way. The results showed that it was used to ward off and contain the negative effects of external turbulent developments, and thereby helped LIMOR to perform better than comparable organizations. Originality/value: As a longitudinal study of the workings and effects of the HPO Framework at a social care and rehabilitation organization, this study is the first of its kind. Moreover, it addresses two gaps in the current literature, by contributing longitudinal evidence to the body of knowledge on improvement techniques, specifically in the non-profit sector, and by adding insights on the practical workings of the HPO Framework in a non-profit context, specifically the social care and rehabilitation sector.